CONSTRUCTION OF DYE-SENSITIZED SOLAR CELLS USING NATURAL PLANTS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Dragon  fruit  dye  has  been  prepared  and  used  in  the  fabrication  of DSSC  as  sensitizer.  The properties  of  dragon  fruit  dye  have  been  investigated  by  UV-Vis  and  FTIR  technique.  The absorption spectrum shows a peak value of 535 nm. Chemically dragon fruit dye shows present of intermolecular H-bond, conjugate C=O stretching and esters acetates C-O-C stretching vibration, which is due to the component of anthocyanin. On the other hand, the resistivity of TiO2  film on ITO  glass before  it  is used  for  the  fabrication  of DSSC  is  also  investigated.  The  TiO2   sheet resistivity increase from 1 layer =  22.1 Ω cm to 2 layers = 369.6 Ω cm. Finally, the efficiency of assemble DSSC was evaluated and simulated using a custom made technique. The result shows fill factor,  Pmax    and  efficiency  during  the  present   of  halogen   lamp  are  0.30,   13  µW,  0.22%, respectively. We have successfully showed that the DSSC using dragon fruit as a dye sensitizer is useful for the preparation of environmental friendly and low-cost DSSC.